MIDDLE DIATHESIS IN OLD JAVANESE LANGUAGE - Ratna Erawati, Ni Ketut; Artawa, Ketut; Pastika, I Wayan; Sri Satyawati, Made (e-Journal of Linguistics, 2014)
Abstract Old Javanese Langusage (OJL) is the language of the archipelago which developed rapidly in the IX-XV centuries. The language has so many alternation verbs in the predicate of the clause structure. Therefore, the problem of the present study is interesting to explore. The term refers to the opinion proposed by Shibatani(1998) and Artawa (2003).Diathesis associated with middle in OJL was found to have three types, namely, the middle diathesis morphological, middle lexical, and middle perifrastic.
Keywords: Stucture, function, semantic, diathesis, and middle.